Phosphorus forms in lowland soils and bioavailability to bean plants - Fernandes, Luiz Arnaldo; Faquin, Valdemar; Neto, Antonio Eduardo Furtini; Curi, Nilton (Pesquisa Agropecuaria Brasileira, 2002)
An experiment was carried out in greenhouse of the Soil Science Department of the Universidade Federal de Lavras, State of Minas Gerais, Brazil, with the objective of verifying the influence of application of limestone and phosphorus on some forms of soil P in four lowland soils cultivated with bean plants. The experimental design utilized was a completely randomized in 4 x 5 x 2 factorial scheme, with four replications, that means: four soils [Gley Humic (GH), Bog Soil (O), Alluvial (A) and Low Humic Gley (GP)], five doses of P (75, 150, 300, 500 and 800 mg dm-3 of P) and two levels of liming (without and with). The soils were incubated during 30 days with limestone and 150 days with phosphorus. After this period, samples of soil were collected to phosphorus fractionation. Each plot was made up of a 3 dm3 pot, where two plants were cultivated until the end of the cycle. By the results obtained, it was verified that the application of limestone and P changed the forms of P in the soils. Except for GP soil, the P labile forms, without and with liming, had a low participation on total phosphorus. Under liming conditions, the P labile is the form of phosphorus preferentially taken up by bean plants.